2005
DOI: 10.1007/s11136-004-6014-y
|View full text |Cite
|
Sign up to set email alerts
|

Validating and norming of the Greek SF-36 Health Survey

Abstract: The main objective of this study was to validate the Greek SF-36 Health Survey and to provide general population normative data. The survey was administered to a stratified representative sample (n = 1426) of the general population residing in the broader Athens area and the response rate was 70.6%. Statistical analysis, according to documented procedures developed within the IQOLA Project, was performed. The missing value rate was very low, ranging from 0.1 to 1.3% at the item level. Multitrait scaling analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
176
2
16

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 222 publications
(219 citation statements)
references
References 17 publications
25
176
2
16
Order By: Relevance
“…All SF-36 mean scale scores (not shown) were lower than the respective general population scores reported in the instrument validation study. 25 Scale internal consistency reliability was high (Cronbach's alpha range: 0.79-0.94) and comparable to (or even exceeding) the corresponding coefficients reported in the developmental study of the instrument 20 and other DFS-SF validations. 36 Item internal consistency and discriminant validity were also high, providing evidence to confirm the hypothesized scale structure of the DFS-SF and to suggest that the translation of the items and the response choices are appropriate.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…All SF-36 mean scale scores (not shown) were lower than the respective general population scores reported in the instrument validation study. 25 Scale internal consistency reliability was high (Cronbach's alpha range: 0.79-0.94) and comparable to (or even exceeding) the corresponding coefficients reported in the developmental study of the instrument 20 and other DFS-SF validations. 36 Item internal consistency and discriminant validity were also high, providing evidence to confirm the hypothesized scale structure of the DFS-SF and to suggest that the translation of the items and the response choices are appropriate.…”
Section: Discussionsupporting
confidence: 73%
“…It was found to have high internal consistency reliability, convergent and discriminative validity and was able to distinguish between groups of respondents in the expected manner (known-groups' validity) on the basis of gender, age, and socioeconomic status. 25 The SF-36 has been shown to discriminate well between perceptions of people with or without one or more chronic diseases 26 and has previously been used to measure HRQoL in greek studies of people with diabetes 27,28 and as a "gold standard" for the validation of the greek diabetes treatment satisfaction questionnaire (DTSQ).…”
Section: Instrumentsmentioning
confidence: 99%
“…19 The Greek version of SF-36 has been found to be valid and reliable for HD patients. 13 Many large studies have demonstrated that QoL is a consistent and powerful predictor of death and hospitalization in HD patients. 20 The Dialysis Outcomes and Practice Patterns Study showed that the PCS score of the SF-36 predicts mortality better than the serum albumin levels.…”
Section: Discussionmentioning
confidence: 99%
“…This version has been found to be valid and reliable. 13 Patients completed the SF-36 questionnaire [International Quality Of Life Assessment Project (IQOLA) SF-36v1 Standard, Greece (Greek)] after every trimester of the study, just before the first dialysis session of the new modality, following the instructions we provided.…”
Section: Sf-36 Qol Scoring Systemmentioning
confidence: 99%
“…Quality of life was assessed by means of the Short-Form Health Survey questionnaire [13, 14]. All patients were asked to report (a) any history of syncope in lifetime and (b) the number of their syncopal episodes during the last 12 months, as suggested by the European Society of Cardiology and the American College of Cardiology [15, 16].…”
Section: Methodsmentioning
confidence: 99%